Odgovornost uprave gospodarske družbe za škodo, povzročeno družbi - Dolenc, Mile (Pravni letopis, 2010)
Obligations of members of the board of directors of a company are not obligations of result, but obligations of care (effort). Basically, the relationship is of a fiduciary nature, as the board of directors is entrusted with the administration of foreign property. The liability of board members is therefore, generally speaking, fault liability. The management is liable for damages incurred by the company for not complying with the diligence of a conscientious and honest businessman. In Germany, which has essentially the same regulation of companies' directors' responsibilities, the Federal Court has adopted the US doctrine of "business judgement rule." Due to the equal characteristics of management's activities in all economies, this doctrine is also suitable for the Slovenian legal system. Concerning the liability for third party influence, Slovenian law differs from the German law only because of an incorrect translation. This error should be corrected as soon as possible.
Keywords: gospodarske družbe; odgovornost; odškodninska odgovornost; uprava; vodenje